Johann Gottlieb Fichte: The Doctrine of the State - Church, Jeffrey (British Society for the History of Philosophy:New Texts in the History of Philosophy, 2024)
The Doctrine of the State is a major work of political philosophy and philosophy of history by one of the most important authors of German Idealism, Johann Gottlieb Fichte. It represents Fichte's final sustained attempt to provide a synoptic overview of his entire system, including a summary of his famously evolving Wissenschaftslehre. The work's overriding concern is with founding the rule of reason in an irrational world. Fichte provides a synoptic account of human history from the dawn of humanity, through the ancient world, and into a modern world governed by a kind of secularized Christianity. His account of humanity's development is one that involves the struggle between faith and reason. Fichte's philosophical analysis of history can be compared to other important works of this period, including works by Friedrich Schelling and G. W. F. Hegel. Written against the backdrop of Napoleon's disastrous defeat in Russia in 1813, the book also revisits the question of the nature and purpose of nationhood and conflict among peoples that Fichte had originally pursued in his important nationalist work, the Addresses to the German Nation. This edition also contains translated excerpts from Fichte's 1813 diary, where his fiery republican resistance to tyranny at home and abroad appear most clearly